Breakfast cereals with inulin obtained through thermoplastic extrusion: Chemical characteristics and physical and technological properties - Ferreira, Suzane Martins; Capriles, Vanessa Dias; Conti-Silva, Ana Carolina [UNESP] (Elsevier, 2021)
Inulin is an interesting dietary fiber with potential to improve the technological and nutritional properties of food products. Thus, the objective of this work was to develop breakfast cereals through extrusion of corn grits with added inulin and evaluating the effects of different extrusion conditions on the chemical, physical and technological characteristics. The independent variables of the experimental design were the moisture of the ‘corn grits and inulin’ mixture (11.5–18.5 g/100 g) and the amount of inulin added (5.1–24.9 g/100 g). The breakfast cereals presented adequate expansion ratio and they maintained their texture after milk addition. Increasing the inulin enhanced the total fructan content and reduced the cutting force after the addition of milk, although increasing together with the moisture of ‘corn grits and inulin’ mixture resulted in higher losses of the total fructans. Decreasing the amount of inulin and increasing the moisture of the ‘corn grits and inulin’ mixture enhanced the color parameters (chroma and hue) and the paste properties (final viscosity and setback). Therefore, the production of breakfast cereals through extrusion of corn grits and inulin is feasible, providing products with fructans in their composition and contributing to consumption of breakfast cereals with fibers.
Keywords: Color; Fructan loss; Paste properties; Response surface methodology; Texture